HACEK-induced endocarditis. (15th May 2013) - Wassef, Nancy; Rizkalla, Essam; Shaukat, Naeem; Sluka, Martin
Abstract : A 61-year-old patient with diabetes had a bio-prosthetic aortic valve replacement 3 years before admission. He complained of lethargy, night sweats, decreased appetite and erratic blood glucose with no weight loss. He had splinter haemorrhage and a systolic ejection murmur at the aortic area. Chest and abdominal examination revealed no abnormality. The erythrocyte sedimentation rate and C reactive protein were raised. He had several sets of blood cultures and he was started on empirical vancomycin, rifampicin and gentamicin. Transthoracic echocardiography showed vegetation on the base of the anterior mitral leaflet, which was confirmed by a trans-oesophageal echocardiography. Blood culture was positive for Haemophilus aphrophilus, and he was started on ceftriaxone for 6 weeks instead of vancomycin and rifampicin and continued gentamicin for 2 weeks. Follow-up echocardiography showed no evidence of vegetations. The patient recovered completely and he was discharged home.